2022
DOI: 10.1021/acscatal.2c00027
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Atom-Level Reaction Kinetics of Carbon-Resistant Bimetallic NiCo-Reforming Catalysts: Combining Microkinetic Modeling and Density Functional Theory

Abstract: In the context of current energy and environmental crises, dry reforming of methane (DRM) is an important reaction. While non-noble metal catalysts are highly promising for real-world DRM applications, they often suffer from deactivation due to sintering and carbon deposition. In this study, ultrafine bimetallic NiCo nanoparticles encapsulated in silicalite-2 (S-2) were prepared via an in situ growth method. Density functional theory in combination with microkinetic modeling was used to understand the influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 58 publications
(102 reference statements)
0
22
0
Order By: Relevance
“…Intrinsic kinetic testing was conducted to exclude internal and external diffusion effects, and the Weisz–Prater criterion (C WP ) and Mears’ criterion (C M ) were used as criteria. C WP < 1 and C M < 0.15 indicate negligible internal and external diffusion effects. , The calculation results presented in Tables S6 and S7 indicated that mass transfer limitations were negligible. As shown in Figure d,e and Table S8, Pd@SiO 2 /ZSM-5-20 exhibits the lowest apparent activation energies ( E a = 23.3 kJ mol –1 ) compared with the other three samples, and its reaction rate ( r ) and turnover frequency (TOF) for HCHO oxidation are the highest at 90 °C and are approximately 15 times higher than Pd/ZSM-5.…”
Section: Resultsmentioning
confidence: 96%
“…Intrinsic kinetic testing was conducted to exclude internal and external diffusion effects, and the Weisz–Prater criterion (C WP ) and Mears’ criterion (C M ) were used as criteria. C WP < 1 and C M < 0.15 indicate negligible internal and external diffusion effects. , The calculation results presented in Tables S6 and S7 indicated that mass transfer limitations were negligible. As shown in Figure d,e and Table S8, Pd@SiO 2 /ZSM-5-20 exhibits the lowest apparent activation energies ( E a = 23.3 kJ mol –1 ) compared with the other three samples, and its reaction rate ( r ) and turnover frequency (TOF) for HCHO oxidation are the highest at 90 °C and are approximately 15 times higher than Pd/ZSM-5.…”
Section: Resultsmentioning
confidence: 96%
“…Moreover, Wang et al combined the density functional theory (DFT) simulations with micro‐kinetics analysis to investigate the synergistic interaction of Ni–Co bimetallic species. [ 138 ] They found that CH 4 and CO 2 had lower dissociation barriers on Ni–Co bimetallic catalysts, contributing to good catalytic activity, and then they designed a Ni–Co@silicate‐2 catalyst without coke formation over 100 h DRM test.…”
Section: Catalyst Design From Active Metalmentioning
confidence: 99%
“…[15] Especially in the last 5 years, there were several studies that developed some novel Ni-Co bimetallic catalysts with significant reactivity in low-temperature DRM reactions and deeply investigated the impacts of Ni-Co alloy on the reaction kinetics and coke resistance of DRM reaction. [127,132,138] By reviewing these studies and comparing them with previous studies about Ni-Co bimetallic catalysts, it was found that the relative ratio of Ni and Co in this bimetallic system played the most important role in directly deciding the catalytic performance of the catalyst in the DRM reaction. [10,15] Based on distinguished support materials, the relative ratio between Ni and Co should be adjusted to achieve better reactivity and coke resistance., Some Ni-Co bimetallic catalysts did not show significant improvement or even did not have better performance compared with monometallic Ni or Co as active sites, despite careful investigation of the optimal Ni/Co ratio.…”
Section: Bi/multi-metal As Active Metalsmentioning
confidence: 99%
“…8). 124 They used excess ethylenediamine to coordinate with the Ni and Co precursors, in order to prevent metal aggregation in the alkaline zeolite crystallization environment. The crystallization, calcination and subsequent H 2 reduction processes generated ultra-small This study provided guidance for the stabilization of bimetallic heterostructures with balanced kinetics at high reaction temperatures.…”
Section: Zeolitesmentioning
confidence: 99%